Iron-Catalyzed Carbenoid Insertion into C(sp3)–H Bonds - Cheng, Qing-Qing; Yang, Ji-Min; Xu, Huan; Zhu, Shou-Fei (Synlett, 2017)
An iron-catalyzed carbenoid insertion into C–H bonds of alkanes was developed with high activity (turnover numbers up to 690 in a gram-scale experiment) and chemoselectivity. This non-heme iron-catalyzed C(sp3)–H insertion reaction provides an efficient strategy for C–H functionalization.
Keywords: iron catalysis; carbenoid insertion; C–H functionalization; chemoselectivity; diazo compounds; alkanes